Collective memories and cultural trauma of different generational groups - Baranova V.A.; Dontsov A.I. (Социальная психология и общество, 2019)
The article theoretically substantiated the approach to the study of cultural trauma through the analysis of memories of generations, characterized by signs of injury. Scientific tasks involved the identification of events that construct two generations of memories of a particular historical period and an analysis of how these events can be characterized as a cultural trauma. The study used survey methods and in-depth interviews. The sample was 83 respondents. The content of collective memories testifies to the marked signs of cultural trauma, which is associated with a certain historical period: for the generation of 1961—1975. These are the events of the late 80s — early 90s, which determine the beginning of changes in the political and economic system: perestroika, the collapse of the USSR; for the generation of “children of war”, this event is the Great Patriotic War and the postwar period. Theoretical analysis and empirical research suggest that cultural trauma is reflected in the memories of generations. The study also recorded post-memory processes, — the attitude of the younger generation to the traumatic events of the twentieth century, which are beyond personal experience.